A NEW LOOK AT THE "AZEKAH INSCRIPTION" - Galil, Gershon (1995)
The "Azekah Inscription" describes the Assyrian campaign of 712 B.C. against Ashdod and Judah. The location of Azekah "between my land and Judah" (line 5), may reflect only a period between 712-701, because (1) Ashdod was turned into an Assyrian province only after 712; (2) according to Sennacherib's Annals, Ashdod was a vassal kingdom in 701; (3) there is no evidence for an Assyrian action against Philistia between 712 and 701. It is therefore clear that there is no possibility to suppose that the "Azekah Inscription" describes Sennacherib's campaign to the West in 701. L'Inscription d'Azekah décrit la campagne assyrienne de 712 av. J.-C. contre Ashdod et Judah. La localisation d'Azekah « entre mon pays et Judah » (ligne 5) ne peut se référer qu'à une période entre 712 et 701, car (1) Ashdod n'a été érigée en province assyrienne qu'après 712; (2) selon les Annales de Sennachérib, Ashdod était un royaume vassal en 701 ; (3) il n'y a pas d'indice de campagne assyrienne contre la Philistie entre 712 et 701. Il est donc clair que l'Inscription d'Azekah ne peut décrire la campagne de 701 de Sennachérib contre l'Ouest.